The Objectives of Maqaṣid al-Shariʻah (American Journal of Islam and Society, 2011)
Along with Islamic finance and jurisprudence for Muslim minorities,Maqaṣid al-Shariʻah (the higher objectives of Islamic Law)completes the trinity of cutting-edge traditional Islamic research.Its importance emanates from its philosophical vision, which allowsfor the practice of divine text and prophetic teachings in a mannerthat acknowledges and responds to contemporary challenges.Recognizing that this vibrant topic is complex, intellectually challenging,and that most books on the subject are written for specialists, theInternational Institute of Islamic Thought published three introductoryguides to provide simple and accessible material for the general reader. The Recognizing that this vibrant topic is complex, intellectually challenging,and that most books on the subject are written for specialists, theInternational Institute of Islamic Thought published three introductoryguides to provide simple and accessible material for the general reader.The series includes the three books above that are the subject of this review.While significantly varying in focus, all three books succeed in providingintroductory-level texts. Muhammed Chapra presents one long argumentthat human well-being and development is realized by enrichingthe human self, faith, wealth, intellect, and posterity. Before moving onin detail to examine the conditions necessary for the enrichment of faith,wealth, intellect, and posterity, and how the Sharʻiah allows people to preservethem all, he cites fourteen different human needs that must be takeninto account in order to enrich and invigorate the human self. Instead, MohammadKamali and Jasser Auda begin with the genealogy of Maqaṣid.After explaining its textual origins, multiple classifications, and the historyof its development, Kamali addresses Maqaṣid theory ‒ following itsexpansion beyond the traditional five objectives (the focus of Chapra’sbook) and describes the main methodological challenges that have facedthe field. Auda departs from Kamali by focusing on the relevance andpromise of Maqaṣid for contemporary Islamic jurisprudence and thought ...